Comparison of Foley’s catheter with PGE2 gel and Foley’s catheter with PGE2 gel with extra amniotic saline infusion for labour induction - Bembalgi, Shobha; ., Lavanya; M. B., Vinutha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Induction of labour is initiation of uterine contractions before the onset in order to vaginally deliver the foetoplacental unit. Common reasons for induction of labour are post-term and hypertensive disorders of pregnancy. The purpose of this study was to compare the efficacy of Foley catheter with intra cervical PGE2 gel and Foley catheter with PGE2 gel with extra amniotic saline infusion for induction of labour. Methods: The clinical trial was conducted from November 2016 to April 2017 at Karnataka Institute of Medical Sciences, Hubballi. 80 pregnant women which included both primigravidae and multigravidae were alternatively divided into two groups. Group 1 received Foley’s and PGE2 gel and group 2 received Foley’s, PGE2 gel and extra amniotic saline infusion for induction of labour. Results: Both groups were comparable with respect to maternal age, gestational age and indication for induction. There was no significant difference in the mean pre-induction Bishop score between two groups. In both the groups there was significant improvement in the Bishop score after 6 hours of induction. But progress in group 2 was greater than group 1(P <0.05). The mean time from induction to delivery in group 2 was shorter and was statistically significant(P<0.05). There was no difference in mode of delivery, neonatal and maternal morbidity and mortality between 2 groups. Conclusions: The present study showed that Foley’s with PGE2 gel with extra amniotic saline infusion is better for labour induction though both groups appear to be effective agents.